K probleme formirovaniya infrastructury sistemy fizicheskoi kul'tury i sporta dlya invalidov - Rubtsova, N. O. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to discuss the main aspects of the problem of infrastructure's creation in the system of physical culture and sport for disabled persons. The author analyses the role and the area of physical education in the system of physical a social rehabilitation of invalids. She emphasises that sport promotes the integration of an invalid into social life by means of the social contacts with other people. The infrastructural components of physical culture and sport system for disabled persons are substantiated and analysed.